2020
DOI: 10.3390/s20247168
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Heart Rate and Respiratory Rate Estimation by Inertial Sensors Embedded in a Virtual Reality Headset

Abstract: Virtual reality (VR) headsets, with embedded micro-electromechanical systems, have the potential to assess the mechanical heart’s functionality and respiratory activity in a non-intrusive way and without additional sensors by utilizing the ballistocardiographic principle. To test the feasibility of this approach for opportunistic physiological monitoring, thirty healthy volunteers were studied at rest in different body postures (sitting (SIT), standing (STAND) and supine (SUP)) while accelerometric and gyrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Floris et al [ 25 ] conducted a similar study in which HR and respiration rate were estimated from signals from an accelerometer and a gyroscope mounted inside a head-worn virtual reality device. Similar to the study by Hernandez et al [ 24 ], in the study by Floris et al [ 25 ], participants wore the device while standing, sitting, and lying down, and the HR was estimated over sliding 10-second windows.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Floris et al [ 25 ] conducted a similar study in which HR and respiration rate were estimated from signals from an accelerometer and a gyroscope mounted inside a head-worn virtual reality device. Similar to the study by Hernandez et al [ 24 ], in the study by Floris et al [ 25 ], participants wore the device while standing, sitting, and lying down, and the HR was estimated over sliding 10-second windows.…”
Section: Introductionmentioning
confidence: 99%
“…Floris et al [ 25 ] conducted a similar study in which HR and respiration rate were estimated from signals from an accelerometer and a gyroscope mounted inside a head-worn virtual reality device. Similar to the study by Hernandez et al [ 24 ], in the study by Floris et al [ 25 ], participants wore the device while standing, sitting, and lying down, and the HR was estimated over sliding 10-second windows. However, unlike the results by Hernandez et al [ 24 ], the results presented by Floris et al [ 25 ] showed more accurate HR estimation when the participants were standing up compared with when the participants were lying down.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most BCG examples that have been previously developed have a gyroscope or an accelerometer placed on the person's chest. Floris et al [25] described how, compared with these chest BCG signals, BCG signals measured from the head or neck have a lower SNR and are more prone to motion artifacts. In the examples of head-worn BCG devices, the authors compensate for this low SNR by taking an average HR over a period of either 8 [14], 10 [25], or 20 seconds [24] instead of measuring an instantaneous HR.…”
Section: Introductionmentioning
confidence: 99%